Validation of a HPLC method for determination of glutamine in food additives using post-column derivatization - Chorilli, Marlus [UNESP]; Salgado, Hérida Regina Nunes [UNESP]; Santos, Fabiana de Santana; Silva, Lucélia Magalhães da [UNESP] (Scientific Research, 2012)
An ion-exchange chromatography (IEC) followed by post-column derivatization method was validated for the determination of glutamine in food additive products. The chromatographic method was carried out on a sodium cation-exchange column and using detection at 570 nm. The mobile phase consisted of sodium eluant, pH 3.15, with 5% sulfolane, sodium eluant, pH 7.40 and sodium column regenerant. The method was linear in the range of 4 - 50 µg/mL (r 2 = 0.9999). The accuracy was 99.78%. Moreover, method validation demonstrated acceptable results for precision and robustness. The method was found to be able to use for routine analysis of the glutamine.
Keywords: Glutamine; Food additive product; Liquid chromatography